Stationarity assessment of resting state condition via permutation entropy on EEG recordings - Alessio Perinelli; Leonardo Ricci (Scientific Reports)
Abstract The analysis of electrophysiological recordings of the human brain in resting state is a key experimental technique in neuroscience. Resting state is the default condition to characterize brain dynamics. Its successful implementation relies both on the capacity of subjects to comply with the requirement of staying awake while not performing any cognitive task, and on the capacity of the experimenter to validate that compliance. Here we propose a novel approach, based on permutation entropy, to assess the reliability of the resting state hypothesis by evaluating its stability during a recording. We combine the calculation of permutation entropy with a method to estimate its uncertainty out of a single time series. The approach is showcased on electroencephalographic data recorded from young and elderly subjects and considering eyes-closed and eyes-opened resting state conditions. Besides highlighting the reliability of the approach, the results show higher instability in elderly subjects, hinting at qualitative differences between age groups in the distribution of unstable brain activity. The method can be applied to other kinds of electrophysiological data, like magnetoencephalographic recordings. In addition, provided that suitable hardware and software processing units are used, the implementation of the method can be translated into a real time one.